1993
DOI: 10.1111/j.1365-2125.1993.tb04218.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age on the pharmacokinetics and pharmacodynamics of single oral doses of benazepril and enalapril.

Abstract: 1. Eighteen healthy, normotensive subjects (nine young and nine elderly) participated in a double‐blind, 3‐way, crossover study to compare aspects of the pharmacokinetics and pharmacodynamics of single oral doses of 10 mg benazepril, 10 mg enalapril and placebo. 2. The hypotensive effect was similar after both drugs but the absolute reductions were greater in the elderly who had higher initial levels of blood pressure. 3. The AUCs for both benazeprilat and enalaprilat were higher in the elderly but by a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The effects of age on the single dose pharmacokinetics and pharmacodynamics of oral benazepril have been reported previously in a comparative study with enalapril [3]. In brief, there were pharmacokinetic differences between young and elderly subjects for both enalapril and benazepril.…”
Section: Introduction Methodsmentioning
confidence: 63%
See 1 more Smart Citation
“…The effects of age on the single dose pharmacokinetics and pharmacodynamics of oral benazepril have been reported previously in a comparative study with enalapril [3]. In brief, there were pharmacokinetic differences between young and elderly subjects for both enalapril and benazepril.…”
Section: Introduction Methodsmentioning
confidence: 63%
“…As with the single dose study [3], there were significant differences between the two age groups in the steady state disposition of benazeprilat. The trough concentrations were significantly higher in the elderly, 37 nmol 1-1 [9].…”
Section: Discussionmentioning
confidence: 79%
“…Reduction in muscle and organ mass, accompanied by increased adipose tissue mass, decreases the Benazepril S10 Kaiser et al [26] Benazepril S10 Macdonald et al [27] Benazepril M10 Creasey et al [ 28 1 Captopril S 100 Williams et al [29] Cilazapril S1 Hockings et al [3O] Enalapril S10 Macdonald et al [25] Enalapril S10 Levinson et al [31] Fosinopril S10 Cirillo et al [32] Lisinopril S20 Gautam et al [ Ramipril S20 Grass et al [38] Spirapril S25 Arner et al [39] Trandolapril S2 M2…”
Section: Comparisons Of Pharmacokinetics In Young and Elderly Patientsmentioning
confidence: 99%
“…A reliable quantitative method that allows a simultaneous determination of the concentration of BZL and BZT in plasma is thus needed. Several analytical methods have been developed, such as high-performance liquid chromatography (HPLC), capillary electrophoresis and an enzymatic method coupled with HPLC or liquid scintillation counting [7,[9][10][11][12]15,16,[18][19][20][21]. Most of these methods, however, are applicable for the purity evaluation of benazepril in bulk drugs and pharmaceutical dosage forms.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been performed to evaluate the pharmacokinetics of BZL in healthy subjects [7,[9][10][11][12][13][14], the elderly [15] and patients with hypertension, major proteinuria, or liver cirrhosis [7,16,17]. Sun et al [9] reported that after a single oral administration of 10 mg benazepril hydrochloride tablet to 12 healthy male Caucasians in South Wales, UK, the mean area under the plasma concentration-time curve (AUC 0-4 h ), maximum plasma concentration (C max ) and time to C max (t max ) values for BZL were 140 ng h/mL, 149 ng/mL, and 0.6 h, respectively; while the mean AUC 0-24 h , C max , and t max values for BZT were 1410 ng h/mL, 257 ng/mL, and 1.5 h, respectively.…”
Section: Introductionmentioning
confidence: 99%